Using object tracking for dynamic video projection mapping - Iwer Petersen (2013)
This document presents a way to realize video projection mapping onto moving objects. Therefore a visual 3D tracking method is used to determine the position and orientation of a known object. Via a calibrated projector-camera system, the real object then is augmented with a virtual texture.